2016
DOI: 10.1111/rssa.12177
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Modelling of Age and Sex Patterns of European Migration

Abstract: Summary. Age and sex patterns of migration are essential for understanding drivers of population change and heterogeneity of migrant groups. We develop a hierarchical Bayesian model to estimate such patterns for international migration in the European Union and European Free Trade Association from 2002 to 2008, which was a period of time when the number of members expanded from 19 to 31 countries. Our model corrects for the inadequacies and inconsistencies in the available data and estimates the missing patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Data on migration come from the IMEM project (Raymer et al 2013; Wiśniowski et al forthcoming), and include age-specific distributions of counts of country-to-country migration for each pair of countries in the EU and European Free Trade Association (EFTA), as well as a residual “rest of world” category, each year from 2002 to 2008. Age-specific death counts for EU/EFTA countries are taken from Eurostat, and, for the rest of the world, are derived from estimates provided by the United Nations (UN) by subtracting deaths in EU/EFTA countries from world totals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on migration come from the IMEM project (Raymer et al 2013; Wiśniowski et al forthcoming), and include age-specific distributions of counts of country-to-country migration for each pair of countries in the EU and European Free Trade Association (EFTA), as well as a residual “rest of world” category, each year from 2002 to 2008. Age-specific death counts for EU/EFTA countries are taken from Eurostat, and, for the rest of the world, are derived from estimates provided by the United Nations (UN) by subtracting deaths in EU/EFTA countries from world totals.…”
Section: Methodsmentioning
confidence: 99%
“…Our work builds on previous research by DeWaard and Raymer (2012) and DeWaard (2013), but with a different and substantially improved set of harmonised age-specific migration flow estimates obtained from the IMEM project, which incorporated a data measurement model, information from experts, and measures of uncertainty (Raymer et al 2013; Wiśniowski et al forthcoming). In what follows, we detail our approach to estimating duration expectancy in EU-15 countries among persons from new-accession countries, including summary measures and the data and model used.…”
Section: Duration Of Residence In the Eu-15 Among New-accession MImentioning
confidence: 99%
“…Previous work of the author together with Jakub Bijak, Joop de Beer, Jon Forster, Peter Smith, Rob van der Erf, and Arkadiusz Wiśniowski contains a larger number of background references for the material presented here and has been used intensively in all major parts of this article [1], [2], [10], [11].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Using such synthetic estimates as a means of understanding migration represents a radically different practice than what currently exists. However, recent research on European migration has shown the advantages of doing so [2], [11], namely a consistent and comparable set of flows that can be used to understand migration processes and to assess migration policies across countries. Considerable efforts will be needed to apply these tools to other regions in the world, where international migration flow data are even sparser.…”
Section: Limitations and Gapsmentioning
confidence: 99%
See 1 more Smart Citation